(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The global rise of resistant bacteria threatens the effectiveness of antibiotics, recommending that herbs’ natural chemical constituents could provide alternative antimicrobial and insecticidal properties. The study evaluated Citrus sinensis peel extracts’ impact on bacterial species isolated from wound samples collected from six hospitals. Quantitative Phytochemical analysis was conducted on the Citrus sinensis peel extracts, Isolates were tested biochemically and molecularly for detection and confirmation of Staphylococcus aureus and Klebsiella pneumonia. The study assessed the antibacterial activity of Citrus sinensis peel extracts using agar disc diffusion method, revealing significant bioactive compounds such as alkaloids, flavonoids, saponins, steroids, glycosides, and tannins. The extracts effectivity against Staphylococcus aureus and Klebsiella pneumonia comes from its bioactive phytochemical components. The result from the morphological and biochemical tests revealed the presence of Staphylococcus aureus, Klebsiella pneumonia, Staphylococcus epidermis, Pseudomonas aeruginosa, Escherichia coli and Enterobacter spp but only Staphylococcus aureus and Klebsiella pneumonia were confirmed by molecular method with a sequence identity of 99.35% and 97.41% respectively when analyzed using the Basic Local Alignment Search Tool (BLAST) of the NCBI package. The study revealed that Citrus sinensis peel extracts showed antibacterial activity against Staphylococcus aureus and Klebsiella pneumonia at different concentrations and Ciprofloxacin as a control. The ethanolic extract showed high activity, while the aqueous extracts showed significant activity. The study suggests Citrus sinensis peel has potential as an antibacterial agent for wound infection treatment, suggesting the need for its phytochemical composition quantification and purification.